IL-33/ST2 axis of human amnion fibroblasts participates in inflammatory reactions at parturition - Wen-jia Lei; Fan Zhang; Yi-kai Lin; Meng-die Li; Fan Pan; Kang Sun; Wang-sheng Wang (BMC, 2023)
Abstract Background Inflammation of the fetal membranes is an indispensable event of labor onset at both term and preterm birth. Interleukin-33 (IL-33) is known to participate in inflammation via ST2 (suppression of tumorigenicity 2) receptor as an inflammatory cytokine. However, it remains unknown whether IL-33/ST2 axis exists in human fetal membranes to promote inflammatory reactions in parturition. Methods The presence of IL-33 and ST2 and their changes at parturition were examined with transcriptomic sequencing, quantitative real-time polymerase chain reaction, Western blotting or immunohistochemistry in human amnion obtained from term and preterm birth with or without labor. Cultured primary human amnion fibroblasts were utilized to investigate the regulation and the role of IL-33/ST2 axis in the inflammation reactions. A mouse model was used to further study the role of IL-33 in parturition. Results Although IL-33 and ST2 expression were detected in both epithelial and fibroblast cells of human amnion, they are more abundant in amnion fibroblasts. Their abundance increased significantly in the amnion at both term and preterm birth with labor. Lipopolysaccharide, serum amyloid A1 and IL-1β, the inflammatory mediators pertinent to labor onset, could all induce IL-33 expression through NF-κB activation in human amnion fibroblasts. In turn, via ST2 receptor, IL-33 induced the production of IL-1β, IL-6 and PGE2 in human amnion fibroblasts via the MAPKs-NF-κB pathway. Moreover, IL-33 administration induced preterm birth in mice. Conclusion IL-33/ST2 axis is present in human amnion fibroblasts, which is activated in both term and preterm labor. Activation of this axis leads to increased production of inflammatory factors pertinent to parturition, and results in preterm birth. Targeting the IL-33/ST2 axis may have potential value in the treatment of preterm birth.